An advanced hybrid fibrous separator by in-situ confining growth method for high performance lithium-ion batteries. (20th November 2022) - Xiao, Wei; Gao, Qian; Duan, Manhua; Cheng, Dan; Yang, Zhanxu
Abstract: Separators with superior electrolyte property and thermal stability are in urgent need for high-performance lithium-ion batteries. This work designs a rational confining polymerization method to fabricate an advanced composite separator, in which poly(cyclotriphosphazene-co-4, 4-sulfonyldiphenol) microspheres (PZSMS) grow directly in poly(vinylidene fluoride) (PVDF) fibrous membrane. To regulate the size and distribution of PZSMS, triethylamine vapor as acid-binding agent is introduced into PVDF membrane separately from the polymeric monomers. This confining strategy promotes the formation of hybrid fibers with PVDF cores and PZSMS shells. The separator comprised of core-shell structured fibers presents better properties than commercial separators. For example, the optimized separator has higher electrolyte uptake of 433%, ionic conductivity of 1.47 mS/cm, mechanical strength of 26.8 MPa, and better interfacial compatibility. Meanwhile, the heat resistance of the robust PZSMS shell endows this separator with lower thermal shrinkage of 1.8% at 150 °C for 0.5 h and preferable flame-retardant property. In LiCoO2 /graphite cells, the optimized separator exhibits a satisfactory capacity retention of 76% at 8.0 C compared with that at 0.5 C and preferable cycling stability with a capacity retention of 97% after 200 cycles. Thus, this PVDF fibrous membrane modified with PZSMS can be a promising candidate for lithium-ion batteries.